2020
DOI: 10.3390/ijms21218183
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Osteoporosis and Nephrolithiasis: Two Sides of the Same Coin?

Abstract: Idiopathic osteoporosis and nephrolithiasis are formidable health problems showing a progressive increase in their incidence and prevalence in the last decades. These temporal trends were observed in both pediatric and adult populations worldwide. Epidemiological and experimental studies indicate that both disorders show several common pathogenic environmental and genetic factors. In this review, we analyzed the clinical characteristics common to the two disorders and the state-of-the-art knowledge regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 146 publications
(170 reference statements)
1
8
0
2
Order By: Relevance
“…Both metabolic syndrome and obesity are recognized risk factors for NL [ 55 ]. A similar pattern was also found in other conditions affecting the mineral metabolism, such as osteoporosis, which can be considered the other side of the same process, as well as a risk factor for NL [ 56 ]. The association with metabolic syndrome was found in this case in women but not in men [ 57 , 58 ], so the current degree of adhesion to the MD pattern observed, in Western countries, may be one of the reasons for the growing incidence of metabolic syndrome, osteoporosis, and NL [ 59 ].…”
Section: Discussionsupporting
confidence: 70%
“…Both metabolic syndrome and obesity are recognized risk factors for NL [ 55 ]. A similar pattern was also found in other conditions affecting the mineral metabolism, such as osteoporosis, which can be considered the other side of the same process, as well as a risk factor for NL [ 56 ]. The association with metabolic syndrome was found in this case in women but not in men [ 57 , 58 ], so the current degree of adhesion to the MD pattern observed, in Western countries, may be one of the reasons for the growing incidence of metabolic syndrome, osteoporosis, and NL [ 59 ].…”
Section: Discussionsupporting
confidence: 70%
“…Epidemiological studies have shown a temporal relationship between idiopathic osteoporosis and kidney stones. In addition, changing dietary patterns, including the ketogenic diet, could possibly be an important environmental trigger in the association, as well [88]. Bone health should be monitored closely in patients on the ketogenic diet and more clinical trials are needed to further define the negative impacts on bone health [89].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers consider idiopathic nephrolithiasis and osteoporosis as two possible manifestations of a unique clinical syndrome. 131,132 Most of the pathogenic factors affect bone by affecting the differentiation, survival and function of osteoblasts and osteoclasts. In addition, these pathogenic factors interact with each other and form a complex etiologic network, which makes the treatment of osteoporosis greatly complicated.…”
Section: Pathogenesis Of Iopmentioning
confidence: 99%
“…With the knowledge about IOP going deep, IOP and nephrolithiasis are believed to be highly connected. Some researchers consider idiopathic nephrolithiasis and osteoporosis as two possible manifestations of a unique clinical syndrome 131,132 …”
Section: Pathogenesis Of Iopmentioning
confidence: 99%